(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the study of various ways to protect information from computer viruses. In the context of the modern digital environment, where cybersecurity threats are becoming more serious, data protection from malware plays a key role. The paper discusses the main methods of protection, including antivirus programs, firewalls, software updates, the use of passwords and data encryption. Current trends and the latest technologies in the field of virus control are also highlighted. The work is aimed at increasing user awareness of data protection methods and contributes to the formation of effective strategies to prevent computer attacks.